## Ask AI on The Internet

You want to solve for the variable 'n'. First, you need to distribute the 3 to both the 'n' and the '-6' inside the parentheses. This can be done like this: 3*n - 3*6 = 18 3n - 18 = 18 For the next step, you have to isolate 'n' by moving -18 to the other side of the equation. You do this by adding 18 on both sides of the equation: 3n = 18 + 18 3n = 36 At that point, to solve for 'n', you have to divide both sides by 3: n = 36/3 n = 12 So the solution to the equation 3(n-6)=18 is n=12.

A new large language model has been made available since this question was asked.

To generate an updated answer from the new model, click the button below.

##### Think your answer is better than the AI's? Post it below.

##### Question Tags

If you want your question answered by an AI, click here.

## Post your own comment: